2000
DOI: 10.1118/1.1287054
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of correction factors for Spencer–Attix cavity theory at photon energies at or above 100 keV

Abstract: To develop a primary standard for 192Ir sources, the basic science on which this standard is based, i.e., Spencer-Attix cavity theory, must be established. In the present study Monte Carlo techniques are used to investigate the accuracy of this cavity theory for photons in the energy range from 20 to 1300 keV, since it is usually not applied at energies below that of 137Cs. Ma and Nahum [Phys. Med. Biol. 36, 413-428 (1991)] found that in low-energy photon beams the contribution from electrons caused by photons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 28 publications
(45 reference statements)
4
62
0
Order By: Relevance
“…15 However, the choice of cross sections is unimportant since the analysis that follows depends upon the ratios of responses to theory which, for graphite chambers, has been shown to be independent of the cross sections if a completely consistent set of cross-section data is used. 3,5 We have confirmed that the same holds true for high-Z chambers within the statistical precision considered here. Under the simulation conditions described above, the K h , K an , and K comp corrections are unity by definition.…”
Section: Iia Egsnrc Calculations Of Chamber Responsesupporting
confidence: 82%
“…15 However, the choice of cross sections is unimportant since the analysis that follows depends upon the ratios of responses to theory which, for graphite chambers, has been shown to be independent of the cross sections if a completely consistent set of cross-section data is used. 3,5 We have confirmed that the same holds true for high-Z chambers within the statistical precision considered here. Under the simulation conditions described above, the K h , K an , and K comp corrections are unity by definition.…”
Section: Iia Egsnrc Calculations Of Chamber Responsesupporting
confidence: 82%
“…Though the electrons below 10 keV contributed to the dose scoring, the stopping power ratios calculated with or without including the track-end effects were agreeable within clinically acceptable range for external photon beams. [28][29][30] Therefore, only the total electron fluence was used in the above stopping-power ratio calculations without explicitly accounting for the track-end effect. The PEGS4 code 18,28 was used to produce the restricted mass-stopping-power ratio between water and the medium, with density corrections based on data from ICRU Report 37.…”
Section: Ratio Of Mass-stopping Powermentioning
confidence: 99%
“…Measurements made by Henry and reported by Shortt and Ross (1986) indicated the need for such a correction factor. A recent re-examination of the effect using Monte Carlo calculations also indicates the necessity for K comp (Borg et al 2000]). As an interim, K comp is shown explicitly in equation (2) but is assigned the value unity.…”
Section: Uncertainty In the Ratio Of The Absorbed Dose To Water Standmentioning
confidence: 99%
“…In the comparison of air kerma standards of NRC and NIST, it was hypothesized that the observed difference of 0.6% may be due to the different methods of estimating this correction . However, further work at NRC on the value of K comp is continuing (Borg et al 2000) and this may alter the NRC's air kerma standard (Rogers et al 2001).…”
Section: Air Kerma Comparisonmentioning
confidence: 99%